ANCIENT RUS ARTISTIC CASTING FROM OLD HALYCH - PUTSKO, Vasyl (Halych. Scientific work collection, 2024)
The article is about a collection of encolpia from Early Medieval Halych, which is kept in the Krylos Museum. The main sights of the museum are imported goods from Kyiv Rus. The most interesting of them are the encolpion with the image of Etimasia (a motif common in the symbolism of the Orthodox Church with the curved throne of the Lord, prepared for the Last Judgment, and the cross representing the Passion of Christ, etc.), as well as the symbols of evangelists connecting the products with the Kyiv artisans of the 11 th century. A small bronze relief depicting a praying archangel is a unique work. The youngest encolpia date back to the early thirteenth century.